2019
DOI: 10.1007/s10825-019-01368-6
|View full text |Cite
|
Sign up to set email alerts
|

Automated netlist generation for 3D electrothermal and electromagnetic field problems

Abstract: We present a method for the automatic generation of netlists describing general three-dimensional electrothermal and electromagnetic field problems. Using a pair of structured orthogonal grids as spatial discretisation, a one-to-one correspondence between grid objects and circuit elements is obtained by employing the finite integration technique. The resulting circuit can then be solved with any standard available circuit simulator, alleviating the need for the implementation of a custom time integrator. Addit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…This convergence result remains consistent regardless of the chosen phase‐space norm. This proof has been originally established for elliptic PDEs, however, we expect a seamless transition to our use case as it has been shown that circuits can be translated into PDEs 28 …”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…This convergence result remains consistent regardless of the chosen phase‐space norm. This proof has been originally established for elliptic PDEs, however, we expect a seamless transition to our use case as it has been shown that circuits can be translated into PDEs 28 …”
Section: Methodsmentioning
confidence: 98%
“…This proof has been originally established for elliptic PDEs, however, we expect a seamless transition to our use case as it has been shown that circuits can be translated into PDEs. 28 It is customary that most of the elements in a circuit are well-known and model representations are available. In this case, various approaches combining exactly known models with data-driven computing have been proposed by the authors in Ref.…”
Section: Computational Costmentioning
confidence: 99%
“…Analogously, this can be done for the rest of the integral Maxwell's equations (2.1), to obtain the discrete primal and dual divergence matrices and the dual curl matrix. For a detailed description of the operator matrices see [113,Appendix A.1], [114], [115].…”
Section: Matrix Constructionmentioning
confidence: 99%
“…The rest of the material matrices are obtained with an analogous averaging procedure. For a description of other material matries see [113, Appendix A.1], [114], [115].…”
Section: Matrix Constructionmentioning
confidence: 99%
See 1 more Smart Citation